Islamic Banks Service Innovation Quality: Conceptual Model - Khan, Tahreem Noor (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
Customer perspectives and satisfaction level are considered important for analysing the performance of Islamic bank service quality. Sufficient researches has been done to explore customer perception and satisfaction level with Islamic banking service quality, however there is lack of data to compare and find the similarity in understanding the main determinant attributes needed for Islamic banking service quality. The purpose of this paper is to describe and integrate the results of existing wealth of research on service quality in Islamic banks. After weighing up all the views from existing research, common findings, concerns will be discussed. This research did not find much of information or studies indicating toward innovation in Islamic banking service quality. Thus based on review of the literature this paper suggests main key attributes of service for Islamic banks (RIBA Service IQ). This research strongly asserts that sincere motivation, truthful intention, dynamic and practical service innovation of quality approaches can uplift Islamic financial brandDOI: 10.15408/aiq.v8i2.3161